The Effect of Brassinosteroid on Pollen Germination and Tube_x000D_ Growth in Three Dianthus Species - (:unkn) unknown (My University, 2019)
In this study, the effect of brassinosteroid on pollen germination and tube growth of Dianthuscalocephalus, Dianthus carmelitarum, and Dianthus deltoides were investigated. Brassinosteroidtreatments did not cause a significant increase in pollen germination of Dianthus calocephalus, while thepollen tube length significantly increased by 8.39% at 0.05 mM, 43.75% at 0.25 mM, 38.40% at 0.5 mMand 7.30% at 2.5 mM in compare the control. Also, brassinosteroid treatments did not cause a significantincrease in pollen germination, and tube length in Dianthus carmelitanum. Although brassinosteroidtreatments did not cause a significant change in pollen tube length in Dianthus deltoides, 0.05 mM, 0.025mM and 0.5 mM brassinosteroid treatments were found to have an increasing effect on pollengermination. Besides, brassinosteroid treatment did not cause a significant change in tube abnormality forall species and all concentration.